The craft sinister : a diplomatico-political history of the Great War and its cause - diplomacy and international politics and diplomatists as seen at close range by an American newspaperman who served in Central Europe as war and political correspondent. - Schreiner, George Abel. (New York)
xxvi, 422 s.